Effects of tooth-brushing force with a desensitising dentifrice on dentine tubule patency and surface roughness. (May 2017) - Mullan, F.; Paraskar, S.; Bartlett, D.W.; Olley, R.C.
Abstract: Objectives: To investigate the effects of a 5% NovaMin containing dentifrice on dentine tubule patency and surface roughness at 100 g and 400 g tooth brush abrasion forces. Methods: 75 polished human dentine samples were prepared and randomly allocated into one of five groups; control (1), Na2 PFO3 100 g abrasion force (2), NovaMin 100 g (3), Na2 PFO3 400 g (4) and NovaMin 400 g (5). The control group underwent two 2-min cycles of artificial saliva (AS), one 2-min erosion cycle; the rest underwent two toothbrush abrasion cycles in an AS/dentifrice slurry and one 2-min erosion cycle. All samples were imaged at baseline and post intervention using Tandem Scanning Microscopy and Profilometry to analyse tubule patency and roughness. Results: Mean tubule patency increased significantly between baseline and post intervention in groups 1, 2 and 4 and decreased significantly post intervention in groups 3 and 5 (p < 0.01). Post intervention, there were statistically significant differences in mean patent tubules between NovaMin and the Na2 PFO3 and control groups (p < 0.001). Surface roughness increased for all groups between baseline and post interventions (P < 0.001); mean (SD) roughness increases for groups 1, 2, 3, 4 and 5 were 0.14 (0.05) μm, 0.18 (0.04) μm, 0.16 (0.06) μm, 0.19 (0.07) μm and 0.21 (0.02) μm respectively. Differences between group 1 and 5 were significant (p < 0.01). Conclusions: Brushing with NovaMin resulted in significant dentine tubule occlusion at 100 g and 400 g, but brushing with Na2 PFO3 resulted in increased tubule patency. Surface roughness increased significantly at 400 g brushing with NovaMin. There was no correlation between tubule patency and surface roughness. Clinical significance: A NovaMin desensitising dentifrice resulted in tubule occlusion even at high brushing forces. There was minimal increase in surface roughness at the lower (100 g) brushing force.